Connecting Ethnomathematics to the Concept of Positive Deviance - Orey, Daniel Clark; Rosa, Milton (Journal of Transformative Praxis, 2020)
An impasse in mathematics education is related to its frequent lack of acknowledgment of local mathematical practices in its research theoretical basis. Pedagogical action of ethnomathematics aids in recording cultural-historical forms of mathematical procedures and practices developed by members of distinct cultural groups. Ethnomathematics is a form of push back from colonization without attempting to replace academic mathematics. Hence, a sense of insubordination triggered by ethnomathematics is creative and often evokes a sense of disturbance that causes a conscious review of rules and regulations endemic to many curricular and educational research contexts. This process enables educators and investigators to adopt positive deviance in developing pedagogical actions that deal with content usually disconnected from the reality of the students in order to deal with imposed norms and rules. Thus, positive deviance involves an intentional act of bending the rules in order to serve the greater good of the school communities.